Euro area time-varying cyclicality of fiscal policy - Afonso, António (2021)
We assess the cyclicality of fiscal policy in the 19 Euro area countries, notably during recessions, for the period 1995-2020. We use a time-varying measure of fiscal cyclicality to describe fiscal policy developments. The results suggest that during recessions discretionary fiscal policy becomes more pro-cyclical, but the overall budget balance becomes more counter- cyclical. Hence, pursuing a Ricardian fiscal regime by more indebted countries leads to higher counter-cyclicality of fiscal policy. Government size reduces counter-cyclicality, as well as trade openness, and financial development has a positive impact on counter-cyclicality.